Priming antibody responses against BRSV induced in beef calves through early vaccination. - Bornheim, Heather Nicole (Kansas State University, 2020)
Bovine respiratory syncytial virus (BRSV) plays an important role in the presentation of bovine respiratory disease (BRD) in young beef calves; however, current vaccination protocols against BRSV have not significantly reduced BRD-associated morbidity and mortality. The objective of this study was to evaluate serum and nasal secretion antibody responses to BRSV in beef calves following vaccination with two different protocols. Within 24-hours-of-life, sixty purebred beef calves were assigned to one of three different treatment groups. Group IN VAC received an intranasal (IN) modified-live (MLV) BRSV vaccine at birth and a subcutaneous (SQ) MLV BRSV vaccine at 2-months. Group SQ VAC received a SQ MLV BRSV vaccine at birth and an IN MLV BRSV vaccine at 2-months while group NO VAC was not vaccinated at birth and received an IN MLV BRSV vaccine at 2-months-of-age. Nasal secretion and serum samples were collected for assessment of BRSV antibodies prior to vaccination at <24 hours, 2-months, and 6-months-of-age. The titers of BRSV antibodies in nasal secretions and serum were similar among treatment groups. At birth, the mean log-transformed BRSV nasal IgA titers were negligible in all groups. At 2-months-of-age, the mean log-transformed BRSV nasal IgA titers in IN-SC VAC, SC-IN VAC, and NO-IN VAC calves were 192.84, 224.49, and 114.71, respectively. At 6-months-of-age, the mean log-transformed BRSV nasal IgA titers in IN-SC, SC-IN, and NO-IN calves were 178.84, 159.33, and 266.62, respectively; however, statistical significance in BRSV IgA titers was not detected among treatment groups at any time point. The model-adjusted mean-Log2 serum BRSV antibody titers were similar among calves from all treatment groups at each sampling point. Early vaccination with MLV BRSV vaccines in a combination protocol at birth and at 2-months-of-age was not different from single IN MLV vaccination at 2-months-of-age inducing nasal or serum BRSV-specific antibody responses in beef calves under the conditions of this study.
Antibody responses induced in beef calves through early vaccination.
Keywords: BRSV; Vaccination; Priming; IgA; Intranasal